Using CRISPR as a Gene Editing Tool for Validating Adaptive Gene Function in Tree Landscape Genomics - Fernandez i Marti, Angel; Dodd, Richard S. (Frontiers in Ecology and Evolution, 2018)
Anthropogenic activities have substantially modified natural forested ecosystems around the world through species exploitation, land-use changes, soil degradation, pollution and introduction of exotic species. The impacts of these activities are being exacerbated today by climate change that is expected to become more severe over the coming decades. Modern landscape genomics has made advances in identifying genes that are associated with phenotypic expression, but they have been unable to prove that the associations are more than correlative. The threats to biological diversity raised by climate change, underscore the need to have an improved understanding of the genetic basis of phenotypic traits. In sedentary, long-lived tree species this becomes of utmost importance, as the success of populations is likely to depend, in large part, on existing standing genetic variation. The most recent technologies of gene editing (CRISPR/Cas9) promise to be an elegant approach that will move forest tree genomics to the next level, by allowing the rigorous testing of gene function and its role in the adaptation of trees to their environment. This perspectives paper looks at how genome editing technologies can be used to advance our understanding of the role genes play in adaptation to climate change in woody plants. We discuss the different CRISPR modes than can be used in studies of adaptive traits in perennial species.